Training on Increasing Structural Officials' Understanding of Unit Cost Calculation at Islamic Hospital Surabaya A. Yani Surabaya - Budhi Setianto; Agus Aan Adriansyah; Yauwan Tobing Lukiyono; Hartatiek Nila Karmila; Muhammad Afwan Romdloni; Effendi Effendi; Mery Susantri; Nikmatus Sa'adah (Journal of Health Community Service, 2025)
Islamic Hospital Surabaya as a Class B Hospital has collaborated with BPJS since 2014. Preparing the tariff pattern used in serving BPJS patients is very important, especially regarding quality and cost control. To do this, hospitals must be able to serve BPJS patients by taking into account existing pricing patterns so that there are no losses in treating patients. To prepare for this, it is necessary to refresh knowledge regarding unit costs and hold a workshop to increase knowledge and calculate unit costs. This workshop is expected to provide additional knowledge to participants regarding hospital business management in determining pricing patterns based on unit cost calculations. The method used in this workshop is to use lecture, case study and simulation methods. 48 participants took part in the workshop with evaluations consisting of pretests and posttests. One important element in streamlining a company's production process is the concept of cost per unit, which can help companies ensure that the costs they incur will be lower than the selling price of one unit. This workshop is very beneficial regarding unit cost calculations, this can be seen from the results of the pretest and post-test calculations with an increase in value of 15% and there is a significant difference between the pre-test and post-test based on the results of the Paired Sample T-Test.